2011
DOI: 10.1007/s10880-011-9271-2
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism Dimensions and Dependency in Relation to Personality Vulnerability and Psychosocial Adjustment in Patients with Coronary Artery Disease

Abstract: The present study sought to illuminate self-criticism and personal standards dimensions of perfectionism and dependency as specific cognitive-personality vulnerability factors that might contribute to a better understanding of numerous psychosocial problem areas that are relevant to coronary artery disease (CAD). One hundred and twenty-three patients diagnosed with clinically significant CAD completed self-report questionnaires. Zero-order correlations and factor analysis results revealed that self-criticism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
2
9
0
1
Order By: Relevance
“…Perfectionism has been identified as a potentially maladaptive trait considered to be a predisposing factor of psychopathology (Dunkley et al, 2011;Enns, Cox, & Clara, 2005;Hewitt & Flett, 1993. But an increasing number of researchers have suggested that perfectionism must be considered as a multidimensional, rather than a unidimensional, construct (Rice & Preusser, 2002).…”
Section: Perfectionismmentioning
confidence: 99%
“…Perfectionism has been identified as a potentially maladaptive trait considered to be a predisposing factor of psychopathology (Dunkley et al, 2011;Enns, Cox, & Clara, 2005;Hewitt & Flett, 1993. But an increasing number of researchers have suggested that perfectionism must be considered as a multidimensional, rather than a unidimensional, construct (Rice & Preusser, 2002).…”
Section: Perfectionismmentioning
confidence: 99%
“…Another goal of this study was to examine the extent to which these personality styles are associated with illness-related coping tendencies. There have been few empirical attempts to examine coping and Type D personality, other than some evidence linking Type D personality with repressive coping (Denollet, 2005) and evidence from Dunkley et al (2012) linking Type D with avoidance coping and low levels of problem-focused coping. Another recent investigation found with a general measure of coping that Type D was again associated with avoidance coping but, somewhat surprisingly, Type D was also associated negatively with emotion-oriented coping (Williams and Wingate, 2012).…”
Section: Type D Personality and Perfectionism In Coping With Cardiac Illnessmentioning
confidence: 99%
“…The authors concluded that both Dependency and Self-Criticism were associated with MDD, severity of depression, and specific depressive symptoms. Dunkley et al (2012) studied Self-Criticism, personal standards and Dependency as specific personality vulnerabilities that might contribute to a better understanding of numerous psychosocial problems relevant to coronary artery disease. Participants were 123 patients diagnosed with coronary heart disease (CHD).…”
mentioning
confidence: 99%